Immunoglobulin G4‐related disease accompanying a small intestinal ulcer: A case. Issue 1 (24th November 2021) - Yoshidome, Yuta; Mizoguchi, Akinori; Narimatsu, Kazuyuki; Takahashi, Shun; Hirata, Dai; Ono, Shinji; Onoyama, Yusuke; Suzuki, Seiya; Horiuchi, Tomoaki; Chiya, Nanoka; Ikeyama, Keisuke; Tahara, Hiroyuki; et al.
Abstract: Immunoglobulin (Ig)G4‐related disease (IgG4‐RD) is a systemic condition associated with fibroinflammatory lesions and is characterized by elevated serum IgG4 levels and IgG4‐positive cell infiltration into the affected tissues. It has been reported that IgG4‐RD affects a variety of organs but uncommonly affects the gastrointestinal tract. In particular, there are few cases of lesions in the small intestine, except for sclerosing mesenteritis, which were mostly diagnosed from surgical specimens. Herein, we describe the case of a 70‐year‐old man who initially presented with abdominal pain, headache, later cognitive decline, and gait disturbance caused by IgG4‐RD. Colonoscopy revealed irregular ulcers in the terminal ileum, and computed tomography of the head showed hypertrophic pachymeningitis. Numerous IgG4‐positive cells were detected in the ileal and dural biopsies. We diagnosed the patient with IgG4‐RD and started steroid pulse therapy. After initiation of treatment, the symptoms quickly improved. The patient was discharged from the hospital after starting oral prednisolone treatment (30 mg). The dosage was gradually reduced to 10 mg. A follow‐up colonoscopy revealed scarring of the ileal ulcers. This case may provide valuable information regarding the endoscopic findings of small intestinal lesions in IgG4‐RD.